THE INFLUENCE OF BRAND IMAGE, SERVICE QUALITY, AND CUSTOMER TRUST ON PURCHASING DECISIONS FOR BUKALAPAK VIRTUAL PRODUCTS - Farras Apikmumtazah (Universitas Mercu Buana, 2026)
This study was conducted with the aim of analyzing the influence of brand image, service quality, and customer trust on purchasing decisions for Bukalapak virtual products. The approach used in this research is a quantitative approach with purposive sampling technique. The sample consisted of 300 consumers who have purchased Bukalapak virtual products in the Tangerang area, and the data was collected through a questionnaire survey via Google Forms. The data analysis technique employed was Partial Least Squares (PLS) using SmartPLS 4.0 software. The results of this study indicate that the variables Brand Image (X1), Price (X2), and Customer Trust (X3) have a positive and significant effect on Purchase Decisions (Y).